Evaluating the effect of MQL technique in grinding VP50IM steel with green carbide wheel - Sato, Bruno Kenta [UNESP]; Lopes, José Claudio [UNESP]; Ribeiro, Fernando Sabino Fonteque; Rodriguez, Rafael Lemes [UNESP]; Domingues, Bruno Biondo [UNESP]; de Souza, Hélio Aparecido [UNESP]; De Angelo Sanchez, Luiz Eduardo [UNESP]; Bianchi, Eduardo Carlos [UNESP] (Springer Nature, 2022)
Usually, the applications of the VP50IM steel demand the grinding process during their manufacturing process (dies for thermoplastics extrusion and molds for thermoplastics injection). Nowadays, grinding is a process that involves high specific energy, highlighting the importance of adopting a method of heat management. Cutting fluids to cool and lubricate the cutting zone is one of the villains of achieving green manufacturing. Therefore, researchers are developing new methodologies to reduce or even eliminate the use of cutting fluids. Minimum quantity lubrication (MQL) was designed to minimize cutting fluid utilization, contributing to an eco-friendly machining process. This paper studies the application of the MQL in the grinding of VP50IM steel using green silicon carbide grinding wheel. The flood condition was the basis of comparison and three feed rates: 0.25, 0.50, and 0.75 mm/min. The analyzed output parameters were: surface roughness, roundness errors, grinding power, grinding wheel wear, microhardness, and metallographic analysis. The best results were provided by the lowest feed rate, since as lower the feed rate, the smoother the cutting process. The surface roughness provided by the MQL was 14% higher than the results provided by the flood condition, which indicates the potential of this new green technique to be adopted in the grinding process.
Keywords: Eco-friendly machining process; Green silicon carbide wheel; Grinding cost; Grinding process; MQL; VP50IM steel